Correction of autonomic nervous system indicators due to the effect of geomagnetic perturbations in patients with remote after effects of closed traumatic brain injury - V. A. Коrshnyak; A. I. Gozhenko; B. A. Nаsibullin (Kazimierz Wielki University, 2016)
Коrshnyak V. А., Gоzhеnkо А. I., Nаsibullin B. А. Correction of autonomic nervous system indicators due to the effect of geomagnetic perturbations in patients with remote after effects of closed traumatic brain injury. Journal of Education, Health and Sport. 2016;6(8):296-304. eISSN 2391-8306. DOI http://dx.doi.org/10.6084/m9.figshare.3749121 http://ojs.ukw.edu.pl/index.php/johs/article/view/3760 https://pbn.nauka.gov.pl/sedno-webapp/works/743659     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.08.2016. Revised 08.08.2016. Accepted: 19.08.2016.     CORRECTION OF AUTONOMIC NERVOUS SYSTEM INDICATORS DUE TO THE EFFECT OF GEOMAGNETIC PERTURBATIONS IN PATIENTS WITH REMOTE AFTER EFFECTS OF CLOSED TRAUMATIC BRAIN INJURY   V. А.Коrshnyak1, А. I. Gоzhеnkо2, B. А. Nаsibullin3   1State Institution "Institute of neurology, psychiatry and narcology of the National Academy of Medical Sciences of Ukraine", Kharkiv, Ukraine 2Ukrainian Scientific and Research Institute of Transport Medicine of the Ministry of Health of Ukraine, Odessa, Ukraine 3The Ukrainian scientific and research institute of medical rehabilitation and balneology of the Ministry of health of Ukraine, Odessa, Ukraine.   Abstract The authors show that in modern biology, life is seen as the ability of living matter, and namely in medicine - the ability of human body, to maintain the existence in natural environment. From this perspective, it is extremely necessary to synchronize the activity of body structures among themselves taking into account the changes of environmental factors. Achieving the harmony between the body activity and environmental changes is carried out using an external pacemaker of life processes' activity, the role of which is performed by the geomagnetic field (GMF).  This became possible due to the fact that the life processes are cyclical, i.e. they possess rhythmic characteristics, and GMF is an electromagnetic field which is changing its characteristics rhythmically.  The material for the present study were the data obtained during the neurological examination of 20 healthy people and 100 patients with remote consequences of CTBI which were treated in the clinic of autonomic nervous system pathology of the SI "Institute of neurology, psychiatry and narcology of the NAMS of Ukraine". The results investigations have showed that geomagnetic perturbations, which modify the GMF parameters, exacerbate the disorders of VNS in patients with remote after effects of CTBI. It is associated with the increased desynchronization of the activity of suprasegmental structures of VNS and with breach of brain vascular system's status that occurs during a magnetic storm. The acupuncture that is aimed at restoring of synchronization of activity of suprasegmental structures of VNS significantly reduces its sensitivity to the geomagnetic disturbances. Keywords: magnetic storm, closed head injury, autonomic nervous system.